Pengarahan Pengelolaan Sistem Informasi Kesehatan Dalam Pengelolaan Data Surveilans Diare - Ni Kadek Armini (Yayasan Kawanad, 2022)
The health information system is one of the six building blocks or main components in the health system in a country. SIK is the main form of the National Health System (SKN) which is used as a component in health-oriented development. An information system that is structured and conceptualized will produce good output and the information is faster, more complete. Information technology is developing rapidly and has an impact on all aspects of life, including health information. One of the health information that has the highest incidence of disease cases among 10 cases of infectious diseases at the bulili health center is diarrheal disease. In order to control and overcome the incidence of disease or health problems and conditions that affect the increase and transmission of diarrheal diseases, it is necessary to provide fast and accurate information in order to direct effective and efficient control and control measures by implementing an integrated surveillance health information system and increasing the number of officers who able to operate a health information system. The counseling activity used a descriptive method with the Human Organization Technology Fit (Hot Fit) approach which was carried out at the Bulili Health Center, Palu City, in November 2021. Based on observations from health education activities about the role of Health Information Systems in managing diarrhea surveillance data, diarrhea surveillance officers have understand the benefits provided by the application of the diarrhea surveillance information system application, one of which is the presentation of information that can be quickly and easily accessed if needed for decision making by stakeholders, although there is still manual data as a result of patients not carrying identity cards.